Investigating the Relation of Glass Ceiling Beliefs and Subjective Career Success: Role of Social Support and Gender - Navneet KAUR; Ella MITTAL (Eurasian Journal of Business and Economics, 2023)
With the advancement in the economy, females' participation in the workforce is increasing but they are still underrepresented in senior positions. So, understanding their psychological viewpoints about the glass ceiling and its association with subjective career success (SCS) is important. This study aims to illuminate the association between glass ceiling beliefs and subjective career success through social support in the Indian healthcare sector. Social support is taken as a mediator in this study. The mediation and moderation approach was used to test the proposed model of the study. For the study, a sample of 300 doctors working in corporate hospitals was surveyed. Data were analyzed through structural equation modeling in AMOS to understand the relationship of all variables. The results found that social support mediates the relationship between optimistic glass ceiling beliefs and career success. Furthermore, the moderating impact of gender was also examined on the association of glass ceiling beliefs and subjective career success. The present study is the first to examine the connection between glass ceiling beliefs and subjective career success in the Indian Health sector through the mediation of social support and gender. Theoretical and practical implications are discussed.